STAT3 activation via interleukin 6 trans-signalling contributes to ileitis in SAMP1/Yit mice. Issue 9 (8th May 2006) - Mitsuyama, K; Matsumoto, S; Rose-John, S; Suzuki, A; Hara, T; Tomiyasu, N; Handa, K; Tsuruta, O; Funabashi, H; Scheller, J; Toyonaga, A; Sata, M
Abstract : Background and aim: SAMP1/Yit mice spontaneously develops intestinal inflammation. Previously, we demonstrated that the signal transducer and activator of transcription (STAT)-3/suppressor of cytokine signalling (SOCS)-3 pathway is pivotal in human inflammatory bowel disease. In our studies in SAMP1/Yit mice, the aim was to investigate whether STAT3 activation contributes to ileitis and to examine the therapeutic effects of this signal blockade. Methods: Intestinal expression of phospho-STAT3 in SAMP1/Yit mice and control AKR/J mice was examined by western blotting and immunohistochemistry. SOCS3 and interleukin 6 (IL-6) mRNA were determined by northern blotting and reverse transcription-polymerase chain reaction, respectively. We also examined the effects of intravenously injected hyper-IL-6, an IL-6/soluble IL-6 receptor fusion protein, and of soluble gp130-Fc, a specific inhibitor of soluble IL-6 receptor signalling, on STAT3 phosphorylation and disease severity in SAMP1/Yit mice. Results: Phospho-STAT3 was expressed strongly during the disease course in SAMP1/Yit mice but only transiently in AKR/J mice. Phospho-STAT3 was localised to epithelial and mononuclear cells in the diseased intestine of SAMP1/Yit mice. SOCS3 as well as IL-6 mRNAs were expressed in affected intestine. Administration of hyper-IL-6 caused disease exacerbation and enhancement of STAT3 phosphorylation. In contrast, soluble gp130-Fc administration ameliorated the disease and suppressed STAT3 phosphorylation. Conclusion: STAT3 signalling is critical in the development of intestinal inflammation in SAMP1/Yit mice. Blockade of this signalling pathway by soluble gp130-Fc may have therapeutic effects in inflammatory bowel disease.